2013
DOI: 10.1128/aac.00048-13
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Efficacy of Macrolides, Minocycline, and Tosufloxacin against Macrolide-Resistant Mycoplasma pneumoniae Pneumonia in Pediatric Patients

Abstract: The importance of macrolide-resistant (MR) Mycoplasma pneumoniae has become much more apparent in the past decade. We investigated differences in the therapeutic efficacies of macrolides, minocycline, and tosufloxacin against MR M. pneumoniae. A total of 188 children with M. pneumoniae pneumonia confirmed by culture and PCR were analyzed. Of these, 150 patients had a strain with an MR gene and 134 had one with an A-to-G mutation at position 2063 of M. pneumoniae 23S rRNA domain V. Azithromycin (n ‫؍‬ 27), clar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
90
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 95 publications
(96 citation statements)
references
References 22 publications
4
90
0
2
Order By: Relevance
“…Recent studies have demonstrated that tetracyclines and fluoroquinolones are effective treatments for patients with macrolide-resistant M. pneumoniae infections (26). In particular, administration of minocycline was shown to decrease the number of DNA copies found in the nasopharynxes of children with macrolide-resistant M. pneumoniae infections (27).…”
mentioning
confidence: 99%
“…Recent studies have demonstrated that tetracyclines and fluoroquinolones are effective treatments for patients with macrolide-resistant M. pneumoniae infections (26). In particular, administration of minocycline was shown to decrease the number of DNA copies found in the nasopharynxes of children with macrolide-resistant M. pneumoniae infections (27).…”
mentioning
confidence: 99%
“…The antimicrobial agents used for MIC determination were as follows: erythromycin, clarithromycin, azithromycin, rokitamycin, clindamycin, minocycline, tetracycline, tosufloxacin, garenoxacin, levofloxacin, and moxifloxacin. The MICs against M. pneumoniae isolates collected in this study were compared with those against MR isolates from pediatric patients that were collected in another study (9).…”
mentioning
confidence: 99%
“…A search for mutations at positions 2063, 2064, and 2617 in the M. pneumoniae 23S rRNA domain V gene region was performed using a direct sequencing method in samples with a positive culture or PCR result, as reported previously (7)(8)(9). The MICs of 11 antimicrobial agents for the M. pneumoniae isolates were determined by microdilution methods (18).…”
mentioning
confidence: 99%
“…Macrolides are used as the first‐line therapy for the treatment of M. pneumoniae infections, especially in children, owing to their high efficacy8 and safety profile 9, 10. However, macrolide resistance of M. pneumoniae, which is acquired by mutations of the ribosomal target of macrolides,11 has been spreading rapidly and widely since 2000,12 resulting in enhanced disease severity with increased complications 13, 14…”
Section: Introductionmentioning
confidence: 99%